2014 International Conference of Educational Innovation Through Technology 2014
DOI: 10.1109/eitt.2014.49
|View full text |Cite
|
Sign up to set email alerts
|

CH-SPOC: A Hybrid Learning Mode and Its Exploration in Zhejiang University

Abstract: MOOC as a type of online education, it integrates the connectivity of social networking, and a collection of freely accessible online resources. Now the online education has entered Post-MOOC era, when various types of online education emerge and improve the development of education. In this paper, we present a new hybrid learning mode based on the concept of MOOC, CH-SPOC, which is applicable for university students. CH-SPOC is a kind of cooperative and hybrid learning for online and offline, which was put in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Also, studies in software engineering, computer network, data structures and algorithms were found, showing the variety of computing topics that SPOCs are applied. Studies about hybrid and blended learning have been performed in courses such as Database Technology and Application [Sui 2017], Information Technology and Teaching [Cheng and Zhang 2014], Computer General [Chen and Zheng 2017]. In these scenarios, students follow their SPOC and present themselves for the proctored exams or face-toface lectures.…”
Section: Resultsmentioning
confidence: 99%
“…Also, studies in software engineering, computer network, data structures and algorithms were found, showing the variety of computing topics that SPOCs are applied. Studies about hybrid and blended learning have been performed in courses such as Database Technology and Application [Sui 2017], Information Technology and Teaching [Cheng and Zhang 2014], Computer General [Chen and Zheng 2017]. In these scenarios, students follow their SPOC and present themselves for the proctored exams or face-toface lectures.…”
Section: Resultsmentioning
confidence: 99%
“…SPOC resources include online lectures, readings, forums, and assessment activities Cheng and Zhang (2014). Online lectures can be delivered via video lessons, lasting between 5 and 10 minutes.…”
Section: Small Private Online Coursesmentioning
confidence: 99%